2021
DOI: 10.1088/1755-1315/886/1/012121
|View full text |Cite
|
Sign up to set email alerts
|

Land suitability assesment for Coffea arabica on the land overgrowed by Uncaria gambir

Abstract: Aornakan I and Kuta Tinggi villages are villages located in Pak-pak Bharat Regency, North Sumatra Province. Currently, the villagers are planting Uncaria gambir and Coffea arabica. This study aimed to evaluate land for cofffe plantations on land overgrown with gambier in Pak-pak Bharat Regency. Sampling was carried out purposively on land overgrown with gambier plants in Aornakan I Village, Pargetteng-getteng Sengkut Sub-district and Kuta Tinggi Village, Salak Sub-district, Pakpak Bharat Regency. The evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Meanwhile, Figure 3 reveals that both Aornakan 1 Village and Kuta Tinggi Village have potential land suitability for S. benzoin of class S2, with the limiting factors being wa and rc. Notably, the average temperature and altitude in these two villages are categorized as S2 (moderately suitable) (Rahmawaty et al 2021c). Previous research in the same villages, Aornakan I Village and Kuta Tinggi Village, indicated that the land was marginally suitable for Coffee arabica cultivation (S3), with the limiting factor being the root medium (rc), particularly soil texture.…”
Section: Styrax Benzoinmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, Figure 3 reveals that both Aornakan 1 Village and Kuta Tinggi Village have potential land suitability for S. benzoin of class S2, with the limiting factors being wa and rc. Notably, the average temperature and altitude in these two villages are categorized as S2 (moderately suitable) (Rahmawaty et al 2021c). Previous research in the same villages, Aornakan I Village and Kuta Tinggi Village, indicated that the land was marginally suitable for Coffee arabica cultivation (S3), with the limiting factor being the root medium (rc), particularly soil texture.…”
Section: Styrax Benzoinmentioning
confidence: 99%
“…Research about kemenyan was conducted by Rahmawaty et al (2021b;2023a) and gambir (Rauf et al 2015;Rahmawaty et al 2021a;2023b) have demonstrated that both kemenyan and gambir share similar land characteristics across various criteria. These findings suggest that both plants have the potential to thrive in the same land units.…”
Section: Styrax Benzoinmentioning
confidence: 99%
See 1 more Smart Citation
“…Altitude can affect media, nutrient retention, water viability, and erosion (Rahmawaty et al 2023). Lowlands have higher light intensity and environmental temperatures than medium and highlands.…”
Section: Ft-ir Analysismentioning
confidence: 99%